Need for mental health care in Isolation and Quarantine: Pandemic perspective from developing countries - Shoib, S; Gupta, AK; Joseph, SJ; Chatterjee, SS; Ahmad, W (Journal of Psychiatrists' Association of Nepal, 2020)
Correction: on 7th April 2021, the following authors were added to this letter: AK Gupta, SJ Joseph, SS Chatterjee, W Ahmad No abstract available.